Analytical dimension of cybersecurity of Ukraine in the conditions of growing challenges and threats (Economics and region, 2022)
The article updates the problem of ensuring cyber security of Ukraine in the conditions of growing challenges and threats in the information space. The question of the formation of additional threats to information resources and technologies in the conditions of rapid transformation of the digital environment is considered (threats associated with cyber attacks, disclosure of personal data, the influence of spyware and viruses, phishing, threats related to updating computer programs, etc.), methods of diagnosis and countermeasures which have not yet been fully developed. It is emphasized that it is information (disinformation) in cyberspace that has become the most important resource and the main immediate driving force. The dynamics of cyber attacks and the level of financial losses of the world economy from the implementation of cyber threats are analyzed. It has been proven that cyber attacks on critical infrastructure of Ukraine and state information resources are a threat to national interests. A statistical analysis of the increase in their intensity at the beginning of 2022 as a component of the implementation of the russian federation's military aggression against Ukraine was carried out. Based on the analysis of Ukraine's position in the global rankings, the country's capabilities in the field of cyber protection were determined, and its cyber power was assessed, i.e., the ability of regulatory measures and means to achieve the strategic goals of cyber security. It has been proven that Ukraine has a high potential in the field of cyber security. At the same time, problematic aspects in the direction of ensuring cyber protection of the national information space are identified. In particular, the low level of contribution to global cyber security, the insufficient level of protection of digital services, and the insufficiently developed direction of military cyber operations were noted. Prospective tasks in the aspect of ensuring Ukraine's cyber security in the face of growing challenges and threats are substantiated, among which it is rightful to note the further improvement of information protection systems of critical infrastructure objects based on world best practices, as well as the coordination of actions with international organizations in countering threats related to development of the digital economy and information society.
Keywords: cybersecurity; information security; challenges and threats; cyber resilience; information environment